Innovator Networks Within the Firm and the Quality of Innovation - Michael Gibbs; Friederike Mengel; Christoph Siemroth (Institute of Labor Economics (IZA), 2025)
Using data from over 28,000 innovators within a firm, we study how network position affects innovation, measured by the quality of ideas proposed in a formal suggestion system. Network degree is associated with higher quality ideas. Bridging across structural holes is negatively related to idea quality in the short run, conditional on degree, but has positive effects in the medium run. Bridging also has positive and persisting effects on the quality of colleagues' ideas, suggesting a positive externality from 'brokers.' Network size is not related to idea quality, after controlling for degree and bridging. Compared to working from the office, remote work leads to lower average network degree and bridging. This weakening of networks may explain the reduced quality of innovation during remote work found in prior literature.
Keywords: D7; D8; O3; 330; networks; innovation; structural holes; network centrality; working from home; hybrid work